The treatment and monitoring of aneurysmal subarachnoid hemorrhage in critically ill patients: Comprehensive neuromonitoring in the management of aneurysmal subarachnoid hemorrhage - Boontoterm, Panu; Sakoolnamarka, Siraruj; Nakla-or, Peera; Phontien, Prateep; Fuengfoo, Pusit (Clinical Critical Care, 2025)
Purpose: To review the treatment and monitoring strategies for aneurysmal subarachnoid hemorrhage (aSAH) in critically ill patients, emphasizing the need for a multidisciplinary approach to stabilize the patient, prevent secondary brain injury, and manage complications. Methods: The review focuses on targeted management of key cerebral parameters, including intracranial pressure (ICP), pressure reactivity index (PRx), cerebral autoregulation (CA), and the integration of non-invasive modalities such as near-infrared spectroscopy (NIRS). These tools are utilized to prevent rebleeding, control ICP, manage cerebral vasospasm, and support systemic homeostasis. Important results: Despite advancements in continuous neuromonitoring and multidisciplinary care, current therapeutic strategies must span the entire treatment continuum from diagnosis and preoperative stabilization to intraoperative management and postoperative recovery. Securing the aneurysm via clipping or coiling remains central to reducing complications and improving neurologic outcomes. Conclusions: Optimal management of aSAH demands individualized and dynamic neuromonitoring strategies. Patients with preserved consciousness may benefit from non-invasive monitoring to detect early deterioration, while those who are comatose or severely impaired require comprehensive invasive monitoring to guide cerebral resuscitation and prevent secondary injuries. Equally important is the strict prevention of systemic complications such as dysglycemia, anemia, hyperthermia, hypoxemia, dysnatremia, and infection, which are critical for maximizing neurologic recovery and survival.